Wearable device to monitor COVID-19 symptoms / Muhammad Izat Irfan Mohd Sam - Mohd Sam, Muhammad Izat Irfan (2021)
There was a wearable system/appliance that monitors the main symptoms of COVID-19. Easy sensors, microcontrollers, and appliances, such as mobile devices and peripherals, were used for the identification and tracking of body temperature, heart rate, breathing rate, and other vital signs that were of great importance in warnings to patients and remote healthcare personnel to great signs of COVID-19 or related diseases. However, in this current situation of pandemic, the healthcare system has been packed with the people that had been affect with this COVID-19 virus. This will make hospital being packed and over flows and due to high number of patients or suspected cases and also PUI, the swab test result will take more time to be confirmed. Therefore, this wearable device will surely ease the burden of the healthcare workers to monitor COVID-19 symptoms. This project is develop using Arduino and contains an Android mobile application in which the healthcare worker is able to easily monitor the PUI or COVID-19 patient and symptoms. Preliminary test results were presented and followed by the basic definition of the measuring theory, system integration, optical signal processing, and networking. The theory was easy and inexpensive, based on our everyday use of materials, but highly resistant to ruins and objects.